PERGESERAN UNIT DAN PROSEDUR PENERJEMAHAN DALAM BUKU HADITH AND HADITH SCIENCES - Nurul Makrifah Faqih; Muhammad Fauzi (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2020)
The book Hadith and Hadith Scienses contains many unit-shifts and has relation with the context of the utterance in the hadith itself. This case encourages the writer to describe the unit-shifts used in the translation of Hadith and Hadith Sciences, and to describe the procedures occurred in the translation which contains the unit- shift in the book of Hadith and Hadith Sciences.The theories are unit-shifts proposed by Catford, and translation procedures introduced by Newmark. Besides, the writer uses supporting theory. That is syntax analysis based on the traditional grammar of English and Arabic. The research methodology in this paper is descriptive-qualitative that is done by doing library research.The writer finds 9 cases of unit-shifts. They are 24 changes of morpheme into word; 4 changes of morpheme into phrase; 1 change of morpheme into clause; 22 changes of word into phrase; 1 change of word into clause; 2 changes of phrase into clause; 1 change of clause into sentence; 4 changes of phrase into word, and 1 change clause into word. In short, the total number of all the unit-shifts is 59. There are 14 procedures found in the analysis. They are 1 synonym, 1 literal translation, 7 compensations, 21 descriptive equivalents, 1 paraphrase, 1 expansion, 8 Additions, 2 class-shifts, 2 modulations, 1 transposition, 1 omission, 1 reduction, 1 triplet (paraphrase + compensation + intra system shift), and 11 couplets.